2012
DOI: 10.1111/j.1468-0084.2012.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Growth in UK Industries: An Intangible Investment Approach*

Abstract: This paper tries to calculate some facts for the "knowledge economy". Building on the work of Corrado, Hulten and Sichel (CHS, 2005,9), using new data sets and a new micro survey, we (1) document UK intangible investment and (2) see how it contributes to economic growth. Regarding investment in knowledge/intangibles, we find (a) this is now greater than tangible investment at, in 2008, £141bn and £104bn respectively; (b) that R&D is about 11% of total intangible investment, software 15%, design 17%, and traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…While it would be possible to develop consistent estimates of the aggregate value of land in the UK, it would be difficult to break this down by industry. 4 It would be possible to expand the number of intangible capital assets beyond software and R&D as has been done for example by Corrado et al (2009), Dal Borgo et al (2013, and…”
Section: Previous Workmentioning
confidence: 99%
“…While it would be possible to develop consistent estimates of the aggregate value of land in the UK, it would be difficult to break this down by industry. 4 It would be possible to expand the number of intangible capital assets beyond software and R&D as has been done for example by Corrado et al (2009), Dal Borgo et al (2013, and…”
Section: Previous Workmentioning
confidence: 99%
“…In recent years, this component became capitalized as an expenditure in order to observe its contribution to GDP. According to Borgo, Goodridge, Haskel & Pesole (2013) asset training, design, and software have the largest shares in knowledge spending especially in the services sector in UK, while R&D has only a small share. Further, Becchetti et al (2003) found that software investment has a complementary effect on skilled labour and increases both labour productivity and the firm efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies of productivity growth that use firm-level data (see, for example, Harris andMoffat, 2015, andDal Borgo et al, 2013) are frequently used to support, shape and fine tune national growth policies. UK government economic policies target productivity at various geographical scales from the national to the regional to the local enterprise partnership.…”
Section: Literature Reviewmentioning
confidence: 99%